Analysis The Effect of Total Quality Management, Technology, and Knowledge Management on Product Quality in Indonesia Construction Industry - Mohammad Yogie Latansa; Tri Joko Wahyu Adi; Mohammad Arif Rohman (Institut Teknologi Sepuluh Nopember, 2019)
The construction industry is being faced with rapid development with a high level of competition. In the current global competition, construction companies must be able to compete in order to meet customer demand and satisfaction. In response to the competition, construction companies must efforts to develop products and services. In the development process knowledge management has a role in improving quality. In addition, the use of technology and the implementation of total quality management through knowledge management can improve quality. Quality is the main factor in order to develop products and services to encourage sustainable achievement. This research aims to analyze the factors that influence technology, implementation of total quality management, and knowledge management on the product construction quality in Indonesia. The data used in this research are primary data. The factor identification process is carried out by distributing questionnaires to contractors which involved in the construction industry in Indonesia as respondents. Furthermore, the data obtained were analyzed using the relative importance index ( RII) to obtain a sequence of factors that influence. Then the influencing factors analyzed using structural equation modelling (SEM) with SPSS statistical software. This research expected to resulting models of factors that influence technology, implementation of total quality management, and knowledge management on product construction quality in Indonesia